Incidence of diverticular disease diagnosed over forty years for colon barium enema. - Viteri Briones, Telmo (Revista Universidad de Guayaquil, 2011)
The regulatory plan and procedural epistemological system system includes formative research academic reality training / research, constitutional considerations and regulations of the Higher Education Act, the Rules of Academic System of the National Higher Education Policy of science and Technology 2007 - 2010 established by the Ministry of Higher Education, Science, Technology and Innovation (SENESCYT), the Strategic Plan of Institutional Development at the University of Guayaquil, the Plan of Management Research and Academic Projects DIPA, and currents of scientific / technological Latin America and the world today, as well as of letters descriptive of the subject Research Methodology I to V classes and administrative paraphernalia required for the process.
Keywords: Formative Research; Seed Research; Multidisciplinary Network-disciplinary systems